(untitled) (Research, Society and Development, 2021)
Objective: Evaluate the eating behavior, influences and perceptions of women after the diagnosis of breast cancer and analyze their nutritional status during cancer treatment. Methodology: Cross-sectional, descriptive, field research with a quantitative approach. Data were collected in two centers from the Women’s Network for Combat to Cancer and in an Oncology Hospital, both in Santa Catarina, with 36 patients, through individual interviews and structured questionnaires developed by the authors. Results: Most participants were overweight and were at risk for metabolic and cardiovascular diseases. Changes in eating habits were reported, as well as instructions on eating behaviors from health professionals. However, the biggest motivations for the changes that occurred were through friends and/or family and the internet. The most prevalent antineoplastic treatment was chemotherapy, accompanied by symptoms such as weakness, nausea and inappetence. A reduction and/or exclusion of sugary/sweet foods, fats, red meat, soft drinks and alcoholic beverages was noticed, and the inclusion of fruits, vegetables, teas, natural juices and water in the diet after diagnosis. Conclusion: It was evident that the predictive nutritional status of metabolic and cardiac diseases prevailed. There was susceptibility to dietary changes, but little influenced by the professionals who accompany them in the treatment, inferring the need for new knowledge exposure strategies, and the constant need for information.